2006
DOI: 10.1080/00480169.2006.36622
|View full text |Cite
|
Sign up to set email alerts
|

Clinical efficacy and tolerance of an extract of green-lipped mussel (Perna canaliculus) in dogs presumptively diagnosed with degenerative joint disease

Abstract: GLME had a beneficial effect on the clinical signs of dogs presumptively diagnosed with mild-to-moderate DJD. Long-term therapy may be required before improvement is apparent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
51
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(52 citation statements)
references
References 11 publications
1
51
0
Order By: Relevance
“…Possibly, the lack of statistical significance of the polydextrose effects is caused by insufficient statistical power in combination with placebo effects rather than by an inefficacy of the supplement. The double-blind nature of the trial excluded any observer bias, but it is well-known that placebo effects occur in double-blind studies on canine osteoarthritis (Dobenecker et al, 2002;Gingerich and Strobel, 2003;Innes et al, 2003;Pollard et al, 2006). Likewise, in this study the clinical signs of the control animals were improved during the course of the study as observed by the owners.…”
Section: Discussionsupporting
confidence: 54%
“…Possibly, the lack of statistical significance of the polydextrose effects is caused by insufficient statistical power in combination with placebo effects rather than by an inefficacy of the supplement. The double-blind nature of the trial excluded any observer bias, but it is well-known that placebo effects occur in double-blind studies on canine osteoarthritis (Dobenecker et al, 2002;Gingerich and Strobel, 2003;Innes et al, 2003;Pollard et al, 2006). Likewise, in this study the clinical signs of the control animals were improved during the course of the study as observed by the owners.…”
Section: Discussionsupporting
confidence: 54%
“…Because of the open nature of the study and the absence of a placebo group, the observed decrease in clinical signs of joint disorders cannot be taken as evidence for a beneficial effect of beta-1,3/1,6-glucans. It is very likely that placebo effects occur when evaluating the clinical signs of dogs with osteoarthritis (Dobenecker et al, 2002;Gingerich and Strobel 2003;Innes et al, 2003;Pollard et al, 2006). This study readdresses the efficacy of a preparation of beta-1,3/1,6-glucans in the treatment of canine osteoarthritis.…”
Section: Introductionmentioning
confidence: 99%
“…In that study, dogs weighing 5 to 15 kg received 3 tablets/day, 16 to 20 kg dogs received 5 tablets/day, 21 to 25 kg dogs received 6 tablets/day, 26 to 45 kg dogs received 8 tablets/day, and 46 to 65 kg dogs received 9 tablets/day. The study showed that 67% of the dogs in the GLM group had improved clinical assessment scores compared to 41% in the placebo (P = 0.018) after 56 days (Pollard et al, 2006). Finally, a study was conducted on dogs suffering from OA (n = 23), with dogs fed a control diet for 30 days before being switched to a test diet enriched with GLM for 60 days (Rialland et al, 2013).…”
Section: Green-lipped Musselmentioning
confidence: 99%
“…All three scores were reduced (P < 0.05) by 36, 33, and 34%, respectively for the GLM group on day 50 compared to baseline (Servet et al, 2006). A study conducted by Pollard et al (2006) tested a GLM supplement with 125 mg/tablet in dogs with OA over 56 days (n = 81; mean age 8.5 years). In that study, dogs weighing 5 to 15 kg received 3 tablets/day, 16 to 20 kg dogs received 5 tablets/day, 21 to 25 kg dogs received 6 tablets/day, 26 to 45 kg dogs received 8 tablets/day, and 46 to 65 kg dogs received 9 tablets/day.…”
Section: Green-lipped Musselmentioning
confidence: 99%
See 1 more Smart Citation